Metallic conduction through van der Waals interfaces in ultrathin $$\hbox{Bi}_2\hbox{Te}_3$$ Bi 2 Te 3 films - Shinichiro Hatta (Nature Portfolio, 2021)
Abstract While the van der Waals (vdW) interface in layered materials hinders the transport of charge carriers in the vertical direction, it serves a good horizontal conduction path. We have investigated electrical conduction of few quintuple-layer (QL) $$\hbox {Bi}_2\hbox {Te}_3$$ Bi 2 Te 3 films by in situ four-point probe conductivity measurement. The impact of the vdW (Te–Te) interface appeared as a large conductivity increase with increasing thickness from 1 to 2 QL. Angle-resolved photoelectron spectroscopy and first-principles calculations reveal the confinement of bulk-like conduction band (CB) state into the vdW interface. Our analysis based on the Boltzmann equation showed that the conduction of the CB has a long mean free path compared to the surface-state conduction. This is mainly attributed to the spatial separation of the CB electrons and the donor defects located at the Bi sites.